Matrix metalloproteinase 8 (MMP8) gene polymorphisms in chronic periodontitis - Izakovicova Holla, L; Hrdlickova, B; Vokurka, J; Fassmann, A (Archives of oral biology, 2012)
OBJECTIVE: Previous studies have suggested that some functional polymorphisms in the matrix metalloproteinase (MMPs) genes are associated with the risk of periodontal disease. However, to date no study has investigated MMP8 gene variants in relation to chronic periodontitis (CP). The aim of this study was to analyse polymorphisms in the MMP8 gene and their associations with microbial composition and clinical manifestation of CP. DESIGN: A total of 619 unrelated Czech subjects were included in the present study. Two polymorphisms [-799C/T (rs11225395) and +17C/G (rs2155052)] in the MMP8 gene were studied in 341 patients with CP and 278 unrelated non-periodontitis controls. Both polymorphisms were detected using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) methods. Subgingival bacterial colonisation (occurrence of bacteria in subgingival pockets and gingival sulci) was investigated by a commercial semiquantitative kit in selected subjects (N=169). RESULTS: Our results showed no differences in the allele and genotype frequencies of the MMP8 -799C/T and +17C/G polymorphisms between patients with CP and controls (p>0.05). Nevertheless, the haplotype T(-799)/C(+17) was significantly more frequent in patients with CP than in controls [43.7% vs. 37.6%, p<0.05, OR=1.273 (95% CI: 1.013-1.601)]. Despite significant differences determined in the occurrence of periodontal bacteria between patients with CP and non-periodontitis controls (from p<0.000001 to p<0.05), no significant relationships between periodontal pathogens, MMP8 polymorphisms and CP were found (p>0.05). CONCLUSIONS: Although none of the investigated SNPs in the MMP8 gene was individually associated with periodontitis, specific haplotype showed association with clinical manifestation of chronic periodontitis in a Czech population.
Keywords: Gene Frequency; haplotypy; polymerázová řetězová reakce; Male; gingiva; Genetic Predisposition to Disease; Bacterial Load; polymorfismus genetický; Česká republika; matrixová metaloproteinasa 8; Sequence Analysis, DNA; sekvenční analýza DNA; Adult; Haplotypes; Case-Control Studies; dospělí; mužské pohlaví; jednonukleotidový polymorfismus; Matrix Metalloproteinase 8; Gingiva; Polymorphism, Genetic; Czech Republic; frekvence genu; chronická parodontitida; Polymorphism, Single Nucleotide; lidé; ženské pohlaví; studie případů a kontrol; Humans; Polymerase Chain Reaction; Female; lidé středního věku; bakteriální nálož; Chronic Periodontitis; genetická predispozice k nemoci; Middle Aged